2003
DOI: 10.2202/1542-6580.1024
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of a Reacting Gas/Solid Flow in the Riser Section of an Industrial Fluid Catalytic Cracking Unit

Abstract: The Fluid Catalytic Cracking (FCC) is an important process in a refinery used mainly to produce higher value gasoline from heavy hydrocarbons. An FCC unit can crack different type of feeds and can use different types of catalysts during its lifetime, which makes this process very flexible and profitable. In this paper, an industrial unit located in Mexico was analyzed and the computational results were compared with available design data. The FCC process involves complex reaction kinetics along with multiphase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…As expected the temperature decreases significantly from the bottom to top of the riser. The variations of the phase temperatures are qualitatively consistent with the literature [23][24][25][26]. Figure 5 shows the temperature in the riser height.…”
Section: Resultssupporting
confidence: 88%
“…As expected the temperature decreases significantly from the bottom to top of the riser. The variations of the phase temperatures are qualitatively consistent with the literature [23][24][25][26]. Figure 5 shows the temperature in the riser height.…”
Section: Resultssupporting
confidence: 88%
“…From Figure 10a, it can be decided that the solids volume fraction rises near the wall and annular flow is observed as in Das et al 3 As seen in Figure 10b, the solids velocity is found to increase over the riser height. This is a consequence of, (i) the cracking of the heavy gas oil into low molecular weight components such as gasoline, LPG, and dry gas, 29, 30, 31 (ii) a higher annular region thickness (see Figure 10b) in the top section of the riser decreasing the effective flow area significantly, and (iii) the gas‐phase pressure in the top section of the riser being lower than the bottom value due to the hydrostatic head of the solid. A low‐pressure in the top section of the riser increases the velocity of the gas phase when compared with the velocity of the gas phase in the bottom section of the riser.…”
Section: Resultsmentioning
confidence: 99%
“…They used kinetic parameters of the fourlump model obtained by Pitault et al 15 An excellent agreement between predicted and observed values is observed in the inlet zone, but large under prediction in the upper section of the riser is clearly seen in Figure 1. Predictions of Benyahia et al 10 improved considerably between 10-25 m of riser height. However, deviation was quite prominent in the inlet and exit regions.…”
Section: Conciliation Attemptsmentioning
confidence: 88%
“…Most of them report that catalytic cracking of hydrocarbon reaction are very fast and conversion takes place within 10-15 m from the inlet of an industrial scale riser. 3,6,[9][10][11] However, Derouin et al 12 observed that actual plant conversion of gas oil and gasoline yield continues to increase significantly up to about 35 m. They correlated industrial data using axial dispersion model, but pointed out that several Additional Supporting Information may be found in the online version of this article.…”
Section: Comparison With Industrial Datamentioning
confidence: 99%